Sushi girl [videorecording (DVD)] - Hamill, Mark; Todd, Tony, 1952-; Duval, James, 1972-; Saxton, Kern (Magnolia Pictures, 2013)
It's Fish's first night out of prison. The four men he has protected with silence invite him to dinner that features an elaborate sushi menu served on a seemingly catatonic, beautiful, naked woman on the dinner table. The thieves can't help but to open old wounds in an attempt to find their missing loot.